2019
DOI: 10.3390/w11081729
|View full text |Cite
|
Sign up to set email alerts
|

Ecological River Health Assessments Using Chemical Parameter Model and the Index of Biological Integrity Model

Abstract: River health is one of the important issues today because of various threats by multiple anthropogenic stressors that have long-term impacts on the physical habitats, biodiversity, ecological functions, and their services. The main objectives of this study is to diagnose the chemical and biological river health in the watershed of Geum River with regard to the chemical regimes (N, P) and fish community using multi-metric chemical pollution index (CPI), and the index of biotic integrity model (IBI), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The observed increase in the COD level appeared to be due to an increase in organic non-biodegradable substances driven by industrial growth and increasing population density, which led to continuous waste inputs into the river [29]. Previous studies have reported that high COD levels are caused by high levels of non-biodegradable organic wastewater, increased inputs of several non-point source pollutants such as humic substances during rainfall, and internal production by algae and aquatic plants [29,42,76]. As with the Yeongsan River, the concentrations of COD are increasing in the Nakong, Han, and Geum Rivers, while BOD is declining [12,42,77].…”
Section: Water Quality Monitoring and Water Quality Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed increase in the COD level appeared to be due to an increase in organic non-biodegradable substances driven by industrial growth and increasing population density, which led to continuous waste inputs into the river [29]. Previous studies have reported that high COD levels are caused by high levels of non-biodegradable organic wastewater, increased inputs of several non-point source pollutants such as humic substances during rainfall, and internal production by algae and aquatic plants [29,42,76]. As with the Yeongsan River, the concentrations of COD are increasing in the Nakong, Han, and Geum Rivers, while BOD is declining [12,42,77].…”
Section: Water Quality Monitoring and Water Quality Indexmentioning
confidence: 99%
“…The resulting clusters of objects show high internal homogeneity (within the cluster) and high external heterogeneity (between clusters). One of the most common CA methods is Bray-Curtis similarity index clustering, which determines the level of similarity between any sample and the entire dataset and is usually illustrated as a dendrogram [42]. The dendrogram offers a visual depiction of the clustering processes and provides a simplified image of the groups and their proximity by dramatically reducing the dimensionality of the original data [6].…”
Section: Cluster Analysis (Ca)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that biological indicators could be used for long-term aquatic ecosystem health assessment. For example, phytoplankton, macrobenthos, fish, and aquatic plants could be used for the characterization of ecosystem health [5][6][7][8]. As one of the most effective tools to characterize human disturbance, the multi-metric index has been widely used all over the world as a more reliable tool as compared to a single index assessment [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have carried out a lot of work in river health index system and its evaluation methods and applied them in various rivers, and obtained many successful experiences. HaRa et al (2019) used the chemical pollution index (CPI) and the index of biological integrity (IBI) to diagnose the chemical system (N, P) and the chemical and biological river health of fish in the Gemu River Basin. Zhang et al (2016) proposed a new concept of lake ecosystem health, a driver-pressure-state-impact-response (DPSIR) management framework, an indicator system of water quality, as well as ecological and socioeconomic criteria to evaluate the lake, Nansi Lake in China.…”
Section: Introductionmentioning
confidence: 99%